2000
DOI: 10.1161/01.res.87.7.566
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Tetrahydrobiopterin Prevents Endothelial Dysfunction and Vascular Oxidative Stress in the Aortas of Insulin-Resistant Rats

Abstract: We have reported that a deficiency of tetrahydrobiopterin (BH(4)), an active cofactor of endothelial NO synthase (eNOS), contributes to the endothelial dysfunction through reduced eNOS activity and increased superoxide anion (O(2)(-)) generation in the insulin-resistant state. To further confirm this hypothesis, we investigated the effects of dietary treatment with BH(4) on endothelium-dependent arterial relaxation and vascular oxidative stress in the aortas of insulin-resistant rats. Oral supplementation of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 28 publications
8
191
1
3
Order By: Relevance
“…It has been reported that several transcription factors, including nuclear factor-κB, have a role in the regulation of Ccl2 expression [27,28]. Using an electrophoretic gel retardation assay, we have previously shown increased binding activity of NF-κB in the aorta and in the heart of fructose-feeding-induced hyperinsulinaemic rats using an electrophoretic gel retardation assay [21]. In addition to the effect on Ccl2 gene, C/EBP-β, and C/EBP-δ regulate the transcription of a number of genes involved in the inflammatory response [8,29].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been reported that several transcription factors, including nuclear factor-κB, have a role in the regulation of Ccl2 expression [27,28]. Using an electrophoretic gel retardation assay, we have previously shown increased binding activity of NF-κB in the aorta and in the heart of fructose-feeding-induced hyperinsulinaemic rats using an electrophoretic gel retardation assay [21]. In addition to the effect on Ccl2 gene, C/EBP-β, and C/EBP-δ regulate the transcription of a number of genes involved in the inflammatory response [8,29].…”
Section: Discussionmentioning
confidence: 85%
“…To examine the effects of insulin on Cebpb, Cebpd and Ccl2 expression in cardiovascular tissues, we studied rats fed on a fructose diet, which show insulin resistance and hyperinsulinaemia [21,22]. As shown in Table 1, the body weight gains of the rats fed on the control diet and the rats fed on the fructose diet were similar over the study period.…”
Section: Characteristics Of Experimental Animalsmentioning
confidence: 99%
“…Endothelial dysfunction has been linked to reduced BH4 availability and uncoupling of eNOS [15,36,37]. Various clinical studies have also demonstrated that administration of BH4 improves endothelial dysfunction in conditions characterized by reduced availability of NO and increased production of reactive oxygen species, such as hypercholesterolemia [38], coronary artery disease [24] and smoking [39].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced BH 4 levels due to oxidative degradation of BH 4 to BH 2 has been reported in diabetes (Shinozaki et al, 2000). Furthermore, BH 2 competes for binding to NOS at the BH 4 site, thus promoting NOS uncoupling and loss of NO production (Katusic et al, 2009).…”
Section: Role Of Oxidative Stressmentioning
confidence: 97%